2009
DOI: 10.1007/s12020-009-9150-x
|View full text |Cite
|
Sign up to set email alerts
|

Cushing’s syndrome caused by an ACTH-producing ovarian steroid cell tumor, NOS, in a prepubertal girl

Abstract: Ectopic ACTH syndrome is a very rare cause of pediatric Cushing's syndrome. And if present, bronchial or thymic carcinoids predominate as causes. We hereby demonstrate a first case report of ACTH-producing ovarian steroid cell tumor, NOS, causing ectopic ACTH syndrome in a prepubertal girl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
1
21
1
1
Order By: Relevance
“…Seidman et al . described an immunohistochemical study of 28 SCT and a substantial number of SCT were positive for cytokeratin Cam 5.2 (46%) and AE1/3 (37%) which was not seen in our observation . Jones et al .…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Seidman et al . described an immunohistochemical study of 28 SCT and a substantial number of SCT were positive for cytokeratin Cam 5.2 (46%) and AE1/3 (37%) which was not seen in our observation . Jones et al .…”
Section: Discussioncontrasting
confidence: 79%
“…Seidman et al described an immunohistochemical study of 28 SCT and a substantial number of SCT were positive for cytokeratin Cam 5.2 (46%) and AE1/3 (37%) which was not seen in our observation. 17 Jones et al also reported that 36% of tumors showed positive expression for AE1/AE3. 18 Although many other published studies have also shown variable diffuse positivity for cytokeratin Cam 5.2 and EMA, none of our cases showed positivity for these immunostains, 13,[17][18][19] and even cytokeratin AE1/AE3 was focally positive in only two cases.…”
Section: Discussionmentioning
confidence: 95%
“…The mean age of diagnosis is 58 years for stromal luteomas and Leydig cell tumors [2], and usually affects younger women for adrenal cortical SCT [2,[8][9][10] and SCT NOS [2,11]. Adrenal-cortical and SCT NOS can present prior to puberty [2,3,8,11], and have even been described in fetuses [12]. In prepuberal girls it can cause isosexual precocity [13,14], with hirsutism, acne, growth-acceleration, clitoral enlargement and pubic hair.…”
Section: Discussionmentioning
confidence: 99%
“…The malignant cells show marked atypia, mitoses, necrosis and hemorrhage. The literature indicates that 25–43% of steroid cell tumor cases are clinically malignant, with 20% of cases found to exhibit metastases outside of the ovary during surgery (2,7). If metastasis is present, ~20% of metastatic lesions usually occur within the peritoneal cavity and rarely occur at distant sites.…”
Section: Discussionmentioning
confidence: 99%